INVESTOR-STATE DISPUTE SETTLEMENT IN INTERNATIONAL PUBLIC LAW: A CRITICAL ASSESSMENT AND FUTURE DIRECTIONS (TAMADDUN NURI JURNALI, 2024)
Investor-State Dispute Settlement (ISDS) is a mechanism that allows foreign investors to bring claims against states in which they have invested, typically through arbitration rather than national courts. Initially conceived as a means to protect investments in politically unstable environments, ISDS has become a central point of debate in international public law. This article offers a critical assessment of ISDS and explores future directions for reform to align the mechanism more closely with modern principles of public international law.